2022
DOI: 10.1155/2022/1839356
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Methicillin-Resistant Staphylococcus aureus Activities of Artocarpus lakoocha Roxb Extract and Its Mode of Action

Abstract: Antibacterial activities and mode of action of Artocarpus lakoocha Roxb extracts against methicillin-resistant Staphylococcus aureus (MRSA) were evaluated, with its biological properties including antioxidant activity and total phenolic content also measured. Heartwoods of A. lakoocha Roxb were extracted by solvents including water, ethanol, acetonitrile, ethyl acetate, isopropanol, and hexane. Results showed that antibacterial activity against MRSA, antioxidant activity, and total phenolic content were highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…The most suitable extraction solvent for obtaining the highest anti- ECC property was ethanol, with a polarity less than that of water but higher than that of hexane. This result indicated that the extraction solvent also plays an important role in the isolation of active components from plants and was supported by earlier studies that determined organic solvents to be typically more effective at extracting antimicrobial compounds than aqueous-based techniques [ 14 , 17 ]. Ethanol extracts from P. betle also demonstrated excellent antibacterial properties over Gram-positive and Gram-negative bacteria, including those classified as multidrug resistant such as metallo- β -lactamase-producing P. aeruginosa and A. baumannii , MRSA, and VRE [ 14 ].…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…The most suitable extraction solvent for obtaining the highest anti- ECC property was ethanol, with a polarity less than that of water but higher than that of hexane. This result indicated that the extraction solvent also plays an important role in the isolation of active components from plants and was supported by earlier studies that determined organic solvents to be typically more effective at extracting antimicrobial compounds than aqueous-based techniques [ 14 , 17 ]. Ethanol extracts from P. betle also demonstrated excellent antibacterial properties over Gram-positive and Gram-negative bacteria, including those classified as multidrug resistant such as metallo- β -lactamase-producing P. aeruginosa and A. baumannii , MRSA, and VRE [ 14 ].…”
Section: Discussionsupporting
confidence: 70%
“…This result concurred with previous studies indicating that plant crude extracts had bactericidal or bacteriostatic properties. The mode of action of the antibacterial agents was identified using the MBC/MIC ratio or time-kill kinetic [ 17 , 25 , 26 ]. If the ratio of MBC/MIC is ≤4, it is defined as a bactericidal agent, with a bacteriostatic mode of action considered when the ratio is ≥4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations